2018
DOI: 10.1021/acs.est.8b00164
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Plutonium(VI) to (V) by Hydroxamate Compounds at Environmentally Relevant pH

Abstract: Natural organic matter is known to influence the mobility of plutonium (Pu) in the environment via complexation and reduction mechanisms. Hydroxamate siderophores have been specifically implicated due to their strong association with Pu. Hydroxamate siderophores can also break down into di and monohydroxamates and may influence the Pu oxidation state, and thereby its mobility. In this study we explored the reactions of Pu(VI) and Pu(V) with a monohydroxamate compound (acetohydroxamic acid, AHA) and a trihydrox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
19
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 49 publications
4
19
2
Order By: Relevance
“…Among the small ligands that have been studied for actinide binding in the environment, the siderophores have garnered significant attention since they are ubiquitous and are strong metal chelators. In particular, the tris-hydroxamate, desferrioxamine B (DFOB), has been extensively studied , and is often taken as a representative molecule of this class of ligands because it is widespread in nature, and it forms very strong complexes with plutonium ,, as well as with the trivalent lanthanides and actinides , (Table S6). It has been proposed that the DFOB complexes could represent as much as ∼30% of the speciation of trivalent lanthanides in seawater, even if present at subnanomolar concentration .…”
Section: Resultsmentioning
confidence: 99%
“…Among the small ligands that have been studied for actinide binding in the environment, the siderophores have garnered significant attention since they are ubiquitous and are strong metal chelators. In particular, the tris-hydroxamate, desferrioxamine B (DFOB), has been extensively studied , and is often taken as a representative molecule of this class of ligands because it is widespread in nature, and it forms very strong complexes with plutonium ,, as well as with the trivalent lanthanides and actinides , (Table S6). It has been proposed that the DFOB complexes could represent as much as ∼30% of the speciation of trivalent lanthanides in seawater, even if present at subnanomolar concentration .…”
Section: Resultsmentioning
confidence: 99%
“…The Pu stock solution was then purified using anion exchange resin (BioRad AG 1 × 8, 100–200 mesh) preconditioned with 8 M HNO 3 . The Pu was loaded on the resin in 8 M HNO 3 , washed with three column volumes of 8 M HNO 3 , and then eluted in 0.1 M HCl. , The final Pu­(IV) concentration in the stock solution was determined to be 8.84 × 10 –8 M. A Pu­(VI) stock was prepared using an electrochemistry method described in previous studies. , Briefly, the purified Pu­(IV) stock was added to an electrochemical cell with 0.1 M NaNO 3 electrode solution at 1.9 V for 5 days.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, these organic compounds can influence the fate and transport of Pu through redox and complexation reactions . Pu­(V/VI) can be rapidly reduced to Pu­(III/IV) by NOM, depending on the nature of the organic matter. , In addition, NOM will complex Pu via carboxylate functionalities and nitrogen groups in both colloidal and particulate phases . Santschi et al revealed that the majority of the remobilized Pu from contaminated soils to streams in storm runoffs, pond discharge, and wind dispersion events at Rocky Flats National Wildlife Refuge was associated with organic macromolecules rather than the more abundant inorganic colloids (iron oxides and clays) .…”
Section: Introductionmentioning
confidence: 99%
“…2). While other recent studies 8,9 have shown that synthetic multidentate chelators can drive the oxidation state of lanthanides and actinides to +IV, Morrison et al 7 demonstrated that even a small bidentate ligand, like acetohydroxamic acid, reduces Pu(VI) to Pu(V) under environmentally relevant conditions, and that the reduction reaction does not produce Pu(IV) or Pu(III). These results raise many questions about the role of commonly occurring natural chelators in environmental samples that are often organic-rich mixtures containing trace amounts of radionuclides.…”
mentioning
confidence: 98%
“…A reference spectra of Pu(IV) DFOB is included showing that the reaction of Pu(VI) with DFOB does not produce any spectral features associated with a Pu(IV) DFOB complex. Adapted with permission from ref 7. .…”
mentioning
confidence: 99%